Prognostic factors for constipation following primary surgery of anorectal malformations in Yogyakarta, Indonesia - Willy Hardy Marpaung; . Rochadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACT Anorectal Malformation (ARM) is a congenital malformation of the anorectal area, occur approximately once in every 5000 live births. There are several morbidities could occur after surgery in ARM. Constipation is the most common morbidity post-surgery in ARM. This study was conducted to evaluate the prognostic factors affecting constipation in postoperative anorectal malformation. This was a case control study involving 74 children who undergo surgery in Dr. Sardjito General Hospital, Yogyakarta from 2008 to 2012. The prognostic factors are sex, type of ARM, age, type of ostomi, type of anoplasty operation, dehiscence of anoplasty, and anal dilatation. There were 41 (55.4%) male patients and 33 (44.6%) female patients in this study. The risk of constipation in the patients with high level ARM was lower than in low level ARM with an OR of 0.150 (95% CI=0.032 - 0.711; p=0.008). Abdominoperineal pullthrough had higher risk for constipation than non abdominoperineal pullthrough (PSARP and ASA) with p = 0.003. The constipation rate was also different between patients with and without dehiscence of anoplasty with an OR of 0.139 (95% CI=0.033 - 0.584; p=0.005). The gender, types of colostomy, types of colon for colostomy, age of primary operation, and frequency of anal dilatation did not affect the constipation rate. In conclusion, postoperative constipation is still a major problem in surgical for anorectal malformations in Yogyakarta. Types of anomaly, primary operative procedures, and dehiscence of anoplasty operation are the prognostic factors that affect the constipation in anorectal malformations.